INVESTIGATION OF SOME VARIABLES ETHICS AWARENESS AND PERSONAL VALUES OF NURSES - Daşbilek, Ferhat; Avşar, Gülçin (AVES, 2019)
Aim: The research was conducted to examine the personal values and ethical sensitivity of nurses in terms of some variables. Method: The sample of the study consisted of 200 clinic/polyclinic nurses who were working at Fırat University Hospital between specified dates and January and February 2016, were not on sick leave/ on leave during data collection stage, and agreed to participate in the study provided they were working in clinic for at least 1 year to strengthen state of the nurses to experience ethical dilemma and their awareness. The data were collected by using; Personal Information Form, Values Hierarchy Scale (HVS) and Moral Sensitivity Questionnaire (MSQ). Results: Total mean score of ethical sensitivity of the nurses was 83.89 ± 19.61 and at moderate level. When the personal value preferences of nurses were compared according to some professional characteristics; it was found that there was a statistically significant difference between nurses' preference of working in the unit, value education status, knowing the existence of ethics committee in the institution, doing their job lovingly, professional association membership status and personal value preference (p<0.05). When the average scores of HVS and sub-dimensions of mean scores were compared according to some professional characteristics of nurses; It was found that there was a statistically significant difference between the nurses' ethical education status, follow-up of ethics publication, love of profession and their own willingness to choose their professions and HVS subscale scores (p<0.05). Conclusion: It was determined as a result of the study that ethical sensitivities of the nurses were at moderate level and they preferred religious values at most. Furthermore, some variables were found to affect ethical sensitivity and personal value preference. © 2019, AVES. All rights reserved.
HEMŞİRELERİN KİŞİSEL DEĞERLERİ İLE ETİK DUYARLILIKLARININ BAZI DEĞİŞKENLER AÇISINDAN İNCELENMESİ*
Keywords: ethical sensitivity; ethics; nursing; personal values